2011
DOI: 10.1089/neu.2010.1568
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Intrathecal Delivery of RhoA siRNA to the Contused Spinal Cord Inhibits Allodynia, Preserves White Matter, and Increases Serotonergic Fiber Growth

Abstract: RhoA is a key regulator of the actin cytoskeleton that is upregulated after spinal cord injury (SCI). We analyzed different methods for siRNA delivery and developed siRNAs targeting RhoA (siRhoA) for SCI treatment. Cy 3.5-labeled siRNA delivered at the time of SCI yielded fluorescence in several cell types in the injury site. Intraspinal injections of chemically stabilized siRhoA into the spinal cord of injured rats reduced RhoA protein levels after 1 week and improved hindlimb walking over 6 weeks. To explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…Comparing the amount and length of regenerating axons of our present study to these previous results, the effects of specific RhoA-downregulation are clearly less pronounced than PTEN and mTOR modulation or C3-treatment and additional lens injury. In line with our results in the optic nerve, RhoA-siRNA applied by intraspinal injections or lumbar puncture had only minor positive effects on motorical outcome in a rat spinal cord injury model although improved sensory function and white matter preservation were reported (Otsuka et al, 2011). …”
Section: Discussionsupporting
confidence: 90%
“…Comparing the amount and length of regenerating axons of our present study to these previous results, the effects of specific RhoA-downregulation are clearly less pronounced than PTEN and mTOR modulation or C3-treatment and additional lens injury. In line with our results in the optic nerve, RhoA-siRNA applied by intraspinal injections or lumbar puncture had only minor positive effects on motorical outcome in a rat spinal cord injury model although improved sensory function and white matter preservation were reported (Otsuka et al, 2011). …”
Section: Discussionsupporting
confidence: 90%
“…A wide range of cationic lipids and polymers, including PEI, polyamidoamine (PAMAM) dendrimers, and poly (β-amino esters) have been evaluated for nonviral delivery of pDNA and small RNA therapeutics [48-50]. Currently, only a few studies have investigated non-viral delivery of siRNA in spinal cord injury models [51-53], non-viral delivery of siRNA in spinal cord injury models [51-53]. Previously, we have reported the synthesis of PgP, a micelle forming block copolymer designed for combinatorial drug/nucleic acid delivery and demonstrated its capability for in vitro transfection of siRNA and pDNA in the presence of serum and pDNA in the uninjured rat spinal cord [39].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to show that polyplexes exhibit increased residence time after local injection into spinal cord lesion site relative to naked siRNA. Several studies have used intrathecal injection and Otsuku et al reported preferential uptake of chemically-modified siRNA at the injury site, presumably due to increased penetration in injured tissue [51] [55]. In the future, we will investigate the delivery of PgP/siRhoA polyplexes to the injured spinal cord by the intrathecal route.…”
Section: Discussionmentioning
confidence: 99%
“…The lentiviral construct for RhoA silencing (lenti-shRhoA) was derived from the siRNA sequence 5′-GCCACUUAAUGUAUGUUAC-3′ (Otsuka et al, 2011) by using the pLVTHM vector. A scrambled control shRNA (lenti-shRhoAscr) was generated using the same vector and the following oligo DNA pair: 5′-CGCGTGGCAAATCTTCTAGTCTATTTCAAGAGAATAGACTAGAAGATTTGCCTTTTTTA-3′ and 5′-CGCGTAAAAAAGGCAAATCTTCTAGTCTATTCTCTTGAAATAGACTAGAAGATTTGCCA-3′.…”
Section: Methodsmentioning
confidence: 99%